Adherence to Statins Therapy of High and Very High Cardiovascular Risk Patients in Real Clinical Practice: Diagnostics and Possible Ways to Solve the Problem (According to the PRIORITY Observational Study) - S. Yu. Martsevich; Yu. V. Lukina; N. P. Kutishenko; N. A. Dmitrieva; S. V. Blagodatskikh; O. V. Lerman; T. A. Gomova; S. I. Drozdetsky; V. V. Skibitskiy; E. A. Kudryashov; N. F. Puchinyan (Столичная издательская компания, 2019)
Aim. To study adherence to treatment with generic statins prescribed to patients with high and very high cardiovascular risk in routine clinical practice, as well as the possible impact of educational training of doctors on compliance with clinical guidelines and changes in patient adherence to treatment. Material and methods. The study was prospective, with educational training for physicians on the main provisions of current clinical guidelines prior to the program. It included 3 visits over 12 weeks: inclusion visit (V0), and visits after 1 and 3 months of follow-up (V1 and V3). The use of generic atorvastatin or rosuvastatin was recommended for all patients. To assess adherence the following surveys were used: medical survey (all visits), the original questionnaire to assess the potential and the actual commitment to taking statins and the causes of non-adherence, and the Morisky-Green 8-question test (visits V0 and V3) to evaluate overall adherence to drug treatment. The patients who started the drug taking according to the medical recommendations and continued it during the study were considered as adherents. Patients who started but stopped taking the drug for 12 weeks were considered as partially non-adherent. Patients who refused to take the recommended statin were considered as non-adherents. The prescribed doses of statins and medical tactics in the titration of doses, as well as the achievement of the target level of low-density lipoprotein cholesterol (LDL cholesterol) were evaluated. Results. 112 (37.5%) of the 298 patients with baseline indications for taking statins did not take these drugs. According to the medical survey at V0 a total of 286 (96%) patients were potential adherents to medical recommendations; at V3 262 (88%) patients were adherent to statin treatment; 34 patients were partially non-adherent, 1 - was non-adherent, and 1 - dropped out of the study immediately after V0. According to the original questionnaire, potential adherence was assessed in 281 patients: 244 (86.8%) were potentially adherent, 37 (13.2%) - partially non-adherent. At V3, out of 294 patients who filled in the original questionnaire, 260 (88.5%) were adherent, 26 (8.8%) - partly non-adherent, 8 (2.7%) - nonadherent. The Morisky-Green questionnaire was filled in by 292 patients: at V0, 106 patients (36.3%) had treatment adherence, non-adherence - 186 patients (63.7%). By V3, an increase in total adherence was found: 159 patients (54.5%) were adherent, and 133 (45.5%) - non-adherent. The lipid profile was evaluated in 231 patients in V1 and in 285 ones - in V3. The target LDL cholesterol level was reached by V1 in 47 (20.3%) patients, and in 184 (79.7%) patients - was not. Dose titration occurred in 56 patients. By V3, 121 (42.4%) patients reached the target level of LDL cholesterol, and 164 - did not. The results of the lipid profile analysis were erroneously interpreted in 21 patients. Conclusion The results of the medical survey and the original questionnaire for assessing adherence predominantly coincided. The Morisky-Green test does not accurately reflect patients' commitment to taking a particular drug. Clinical inertness of doctors in the titration of statin doses and achievement of target LDL cholesterol levels were found as well as erroneous interpretation of the LDL cholesterol level. Educational trainings for doctors had a positive effect on the implementation of clinical guidelines, and also contributed to increasing patient adherence to medical recommendations.